PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA - Dyah Shinta Kusumaningtyas; Abdul Kodir Zaelani; Joelianti Dwi Supraptiningsih (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2025)
Financial reports are a means to present in a structured manner the financial position and financial performance of an entity. Quantitative research is used to research a specific population or sample whose data collection uses research instruments, quantitative data analysis with the aim of testing the established hypothesis. The data to be used in this study is secondary data. Secondary data is data obtained other than from respondents who are the target of the study. The partial test results state that the tax planning variable shows a positive regression coefficient of 0.066 and a calculated t value of 1.742 with a significance value of 0.030 ˂ 0.05. So it can be concluded that partially tax planning has an effect on profit management. In the linear regression equation above, the regression coefficient value of deferred tax burden is 0.672. The resulting value is positive, which means it indicates a one-way influence between the dependent variable of profit management and the independent variable of deferred tax burden. The simultaneous test results state that tax planning and deferred tax burden on profit management show a significance value of 0.021, which is smaller than 0.05. So it can be concluded that tax planning and deferred tax burden together (simultaneously) have an effect on profit management. For further research, it is recommended to add more variables, then add companies from other sectors or use all company sectors as research objects and to be able to increase the research period.